1978
DOI: 10.1073/pnas.75.11.5301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thyroid phospholipids on the interaction of thyrotropin with thyroid membranes.

Abstract: Various lipids extracted from bovine thyroid glands were tested for their ability to affect the binding of -25I-labeled thyrotropin to bovine thyroid membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Other studies found no effect of added gangliosides on TSH binding when assayed under physiological conditions (21), in agreement with observations on the binding of human chorionic gonadotropin to testicular membranes (37). Thus, numerous studies (2)(3)(4)(5)20) have demonstrated that, under nonphysiological conditions, gangliosides can inhibit TSH binding to thyroid membranes, but this appears to involve the low-affinity site. When gangliosides are directly incorporated into thyroid cells, they do not cause increased binding under physiological conditions.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Other studies found no effect of added gangliosides on TSH binding when assayed under physiological conditions (21), in agreement with observations on the binding of human chorionic gonadotropin to testicular membranes (37). Thus, numerous studies (2)(3)(4)(5)20) have demonstrated that, under nonphysiological conditions, gangliosides can inhibit TSH binding to thyroid membranes, but this appears to involve the low-affinity site. When gangliosides are directly incorporated into thyroid cells, they do not cause increased binding under physiological conditions.…”
Section: Discussionsupporting
confidence: 69%
“…Other Methods. Mixed brain gangliosides were isolated from bovine brain and exhaustively purified to remove any contaminating phospholipids (5 ponents of FRTL cells were labeled by NaIO4 oxidation followed by NaB3H4 reduction, the same three gangliosides were observed to be labeled (Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have provided evidence indicating that plasma membrane lipids in thyroid glands modulate the TSH receptor and its ability to bind TSH (Bashford et al 1975, Mehedi et al 1977, Omodeo-Sale et al 1978, Aloj et al 1979. Furthermore, an important role for phospholipids has been indicated in the TSHresponsive adenylate cyclase system (Macchia et al 1970, Yamashita et al 1970, Yamashita & Field 1973, Moore & Wolff 1974, Amir et al 1976.…”
Section: Treatment Without Epa-e (Days)mentioning
confidence: 99%
“…This possibilities has also been pointed out previously by Omodeo-Sale et al (1978). The ganglioside fractions containing two sialic acids per molecule are the most active fractions in inhibiting [125I]TSH binding to thyroid plasma membranes.…”
Section: Discussionmentioning
confidence: 62%